Lineage marker synchrony in hematopoietic genealogies refutes the PU.1/GATA1 toggle switch paradigm - Michael K. Strasser (Nature Portfolio, 2018)
The timing of cell fate choices is usually unknown, because we have to rely on indirect evidence of their molecular basis. Here, the authors introduce a method to infer decision times from marker onset in cell genealogies, and find evidence refuting the paradigmatic PU.1/GATA1 cell fate switch.